Complications and mortality following percutaneous and laparoscopic liver biopsy: A multicenter study in a resource‑limited healthcare system - Nadieh Abdallah; Ahed Almahdi; Diana Shella; Rasha Al-Masri; Iyad Maqboul; Mohammad Jaber; Ramzi Shawahna (PLoS ONE, 2026)
This study was conducted to assess the incidence and types of complications and mortality following liver biopsy, and to identify independently associated factors that can inform clinical practice in a resource‑limited healthcare system. A retrospective multicenter study was conducted across six major hospitals between January 2020 and December 2025. Medical records of 218 patients undergoing percutaneous and laparoscopic liver biopsies were reviewed. Demographic, clinical, laboratory, procedural, and outcome variables were extracted using a validated data collection form. Inferential analyses were conducted using chi‑square, Fisher’s exact, and Mann‑Whitney U tests, while multivariate logistic regression models were employed to identify factors independently associated with complications and mortality. The most common types of complications were infection (n = 7, 3.2%) and hemorrhage (n = 6, 2.8%), followed by pulmonary complications (n = 4, 1.8%), metabolic disturbances (n = 3, 1.4%), and acute kidney injury (n = 2, 0.9%). Mortality was recorded in 6 patients (2.8%). Higher pre-operative white blood cell count was independently associated with infections (OR: 1.28, 95% CI: 1.02–1.62, p = 0.036). Older age was independently associated with mortality (OR: 1.07 per year increase, 95% CI: 1.01–1.15, p = 0.035). Hemorrhage and pulmonary complications were more frequent after laparoscopic biopsy and under general anesthesia, although these associations did not remain significant in adjusted models. This study provides the first systematic evidence on liver biopsy safety in Palestine, a resource‑limited healthcare system, thereby filling a critical gap in the regional literature. The study identified pre-operative increases in white blood cell count as a predictor of infection and older age as a predictor of mortality. These simple, pragmatic markers can guide monitoring and risk stratification in constrained environments, offering actionable insights for clinicians and policymakers. Future studies should be conducted to evaluate whether these markers can help reduce complications and mortality.